Application of the WetSpass simulation model for determining conditions governing the recharge of shallow groundwater in the Poznań Upland, Poland - Graf, Renata; Przybyłek, Jan (Geologos, 2018)
Assessments of the infiltration recharge of groundwater are performed using various methods and on different scales. Infiltration is dependent of climatic factors, aspects of water circulation, as well as on quasi-stationary and variable environmental features of a specific area, which are frequently difficult to determine on the basis of direct measurements or observations. The objective of the present study was to identify factors conditioning recharge of shallow groundwater in selected catchment areas of the Poznań Upland using the WetSpass simulation water balance model with spatially distributed parameters. Our analysis has indicated favourable and unfavourable conditions for recharge of groundwater in the annual period and in both half-year periods, which are the result of mutual relationships between the physical qualities of these catchment areas and their climatic and hydrological characteristics. The results obtained also confirmed the impact of surface runoff and actual evapotranspiration on the spatial distribution of effective infiltration. With soil types and groundwater depth distributions being similar in the catchment areas, changes in relationships between components of water balance are caused by differences in the type of land usage. Application of the WetSpass model has made it possible to arrive at a more accurate assessment of groundwater recharge. The results obtained may be used for erification of recharge areas and values of effective infiltration, set as a boundary condition in groundwater flow models.